Research on the Occupational Noise Exposure Health Risk Management Standard - Minyan Li; Deyin Huang; Qian Zhang (Journal of Risk Analysis and Crisis Response (JRACR), 2018)
To prevent and control the occupational noise hazard, procedures and methods of risk assessment and management of occupational noise hazard in the workplaces have been proposed as technical guidelines in the new standard “Risk Management Guidelines for Noise Occupational Disease Hazard” based on the current status and technical requirements of occupational noise hazard in China. These guidelines are consist of the risk assessment method which partly adopts the method given by the latest ISO 1999:2013(E) “Acoustics — Estimation of noise induced hearing loss”, and the risk management procedures which are mainly based on the US NIOSH's recommended standard "Occupational Noise Exposure Revised Criteria 1998" . The guidelines put forward procedures and technical contents such as the risk management program, occupational noise exposure quantitative risk evaluation procedures and methods, and the implementation details of a hearing conservation plan. The standard is based on the current status and technical requirements of the occupational noise hazard in China, in accordance with the relevant national laws, regulations and standards related to hearing protection and supervision and management of the occupational hazard of construction projects. It can be used as guidelines for occupational noise exposure evaluation and risk assessment in various kinds of workplaces that produce productive noises and for exposure level monitoring, effectiveness evaluation of noise control measures, occupational health management, supervision and inspection.